E-LEARNING PROBLEMS IN ARABIC LANGUAGE AND ISLAMIC COURSES DURING THE CORONA PANDEMIC - Nasser Rady Al-Zuhri Ibrahim, Adel Abdel Fadeel Eid bleek (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This topic deals with the problems of e-learning in Arabic language and Islamic courses in educational institutions in Wadi Al-Dawasir and the problems faced by faculty and students in distance education. And how to overcome these problems and the role of government institutions, faculty members and students in overcoming these problems and responding to the Corona pandemic in a way that guarantees the safety of the educational process, and makes use of the electronic study experience in Wadi Al-Dawasir. Monitoring e-learning problems in Arabic and Islamic language courses and presenting the problems of Wadi Al-Dawasir during the pandemic, providing the solutions that the research sees during confronting the problem, and monitoring the positive solutions that have been made on the ground. Also providing support to faculty members in solving problems through what the research proposes of solutions it deems appropriate, and monitoring the positive aspects of distance education in this region and the time of the pandemic. The research consists of an introduction, three topics, and a conclusion that includes the most important results, the first topic deals with the advantages of distance education, and the second topic includes the general and specific negatives that faced students and faculty members in their decisions in Arabic language and Islamic studies, and the third topic : Problems of electronic tests in Arabic language and peace studies courses, then the conclusion, and dealt with the most important results and recommendations. The research adopts the descriptive approach, describing problems and their dimensions, and proposing solutions to them. One of the most important results of the research is monitoring e-learning problems during the Corona pandemic in Wadi Al-Dawasir with regard to Arabic language and Islamic courses and electronic testing problems and proposing appropriate solutions for it. The study recommended the necessity of motivating students to study remotely and continuing it after the end of the Corona pandemic, even partially with Traditional education.